2006
DOI: 10.1093/bib/bbl016
|View full text |Cite
|
Sign up to set email alerts
|

Partial least squares: a versatile tool for the analysis of high-dimensional genomic data

Abstract: Partial least squares (PLS) is an efficient statistical regression technique that is highly suited for the analysis of genomic and proteomic data. In this article, we review both the theory underlying PLS as well as a host of bioinformatics applications of PLS. In particular, we provide a systematic comparison of the PLS approaches currently employed, and discuss analysis problems as diverse as, e.g. tumor classification from transcriptome data, identification of relevant genes, survival analysis and modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
512
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 675 publications
(514 citation statements)
references
References 79 publications
1
512
0
1
Order By: Relevance
“…S2. The partial leastsquares regression approach is beneficial because it uses the continuous spectrum as a single measurement rather than in a band-by-band type of analysis (70,71). Across 79 1-ha field plots in Peru, Asner et al (16,17) showed that LMA could be retrieved with an uncertainty (root mean squared error or RMSE) of 11.8 g m −2 across a LMA range of 76-180 mg g −1 .…”
Section: Methodsmentioning
confidence: 99%
“…S2. The partial leastsquares regression approach is beneficial because it uses the continuous spectrum as a single measurement rather than in a band-by-band type of analysis (70,71). Across 79 1-ha field plots in Peru, Asner et al (16,17) showed that LMA could be retrieved with an uncertainty (root mean squared error or RMSE) of 11.8 g m −2 across a LMA range of 76-180 mg g −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Weights, however, are a nonlinear combination of predictor and response variables (Nguyen & Rockeb, 2004). There are approaches (Liu & Rayens, 2007;Boulesteix & Strimmer, 2006;Fort & Lambert-Lacroix, 2005;Nguyen & Rockeb, 2004;Man et al, 2004;Huang et al, 2005) applying the original PLS to categorical, binary responses. However, research confirms that it is better to use PLS procedures adjusted to binary responses (Nguyen & Rockeb, 2002).…”
Section: Dealing With High Dimensionalitymentioning
confidence: 99%
“…Also, weights are dependent on sample predictor variances and the partial correlation coefficient (Garthwaite, 1994;Nguyen & Rockeb, 2004). PLS is also used in conjunction with Linear Discriminant Analysis (LDA) (Boulesteix & Strimmer, 2006;Boulesteix, 2004;Liu & Rayens, 2007). Fort and Lambert-Lacroix (Fort & Lambert-Lacroix, 2005) proposed a combination of the PLS and Ridge penalty.…”
Section: Dealing With High Dimensionalitymentioning
confidence: 99%
“…The PLSGLR method chooses latent components and considers the response variable in regression, which is different from similar methods, such as principal component regression [44].…”
Section: Feature Rankingmentioning
confidence: 99%